The effect of malaria on childhood anemia in a quasi-experimental study of 7,384 twins from 23 Sub-Saharan African countries - Starck, Tim; Dambach, Peter; Rouamba, Toussaint; Tinto, Halidou; Osier, Faith; Oldenburg, Catherine E.; Adam, Maya; Bärnighausen, Till; Jaenisch, Thomas; Bulstra, Caroline A. (Frontiers in Public Health, 2022)
Background Young children in sub-Saharan Africa (SSA), particularly those from resource-limited settings, are heavily burdened by anaemia and malaria. While malaria infected children frequently become anaemic (haemoglobin < 110g/L), anaemia is a strongly multifactorial disease with many other risk factors than malaria. Due to the complex and often overlapping contributors to anaemia, it remains challenging to isolate the true impact of malaria on population level haemoglobin concentrations. Methods We quantified the malaria-induced effect on haemoglobin levels in children under 5 years of age, leveraging data from 7384 twins and other multiples, aged 6 to 59 months, from 57 nationally representative Demographic and Health Surveys (DHSs) from 23 SSA countries from 2006 to 2019. The quasi-experimental twin fixed-effect design let us minimize the impact of potential confounders that do not vary between twins. Results Our analyses of twins revealed a malaria-induced haemoglobin decrease in infected twins of -9 g/L (95% CI -10; -7, p < 0.001). The relative risk of severe anaemia was higher (RR = 3.01 , 95% CI 1.79; 5.1, p < 0.001) among malaria positive children, compared to malaria negative children. Conversely, malaria positive children are only half as likely to be non-anaemic (RR = 0.51, 95% CI 0.43; 0.61, p < 0.001). Conclusion Even after rigorous control for confounding through a twin focussed study design, malaria substantially decreased haemoglobin levels among SSA twins, rendering them much more susceptible to severe anaemia. This effect reflects the population-level effect of malaria on anaemia.